2021
DOI: 10.51694/advweedsci/2021;39:00005
|View full text |Cite
|
Sign up to set email alerts
|

Soil solarization improves soil fertility in addition to weed management in sesame under subtropical conditions of Pakistan

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided that the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…Similar TSSC and TA results were recorded by Qiu et al [37] in hot peppers, and by Patil et al [38] in bell peppers. The explanation probably lies in the reduced water accumulation [39] and the increased accumulation of Na, K, and Cl in fruits induced by salinity [40]. Interestingly, in this study no significant impact on fruit firmness was found in pepper plants subjected to salinity stress, in line with the results of Salinas et al [34].…”
Section: Discussionsupporting
confidence: 87%
“…Similar TSSC and TA results were recorded by Qiu et al [37] in hot peppers, and by Patil et al [38] in bell peppers. The explanation probably lies in the reduced water accumulation [39] and the increased accumulation of Na, K, and Cl in fruits induced by salinity [40]. Interestingly, in this study no significant impact on fruit firmness was found in pepper plants subjected to salinity stress, in line with the results of Salinas et al [34].…”
Section: Discussionsupporting
confidence: 87%